Response of non-linear shock absorbers-boundary value problem analysis - Rahman, Muhammad Ashiqur; Ahmed, Umama; Uddin, M.S. (Zielona Góra: Uniwersytet Zielonogórski)
A nonlinear boundary value problem of two degrees-of-freedom (DOF) untuned vibration damper systems using nonlinear springs and dampers has been numerically studied. As far as untuned damper is concerned, sixteen different combinations of linear and nonlinear springs and dampers have been comprehensively analyzed taking into account transient terms. For different cases, a comparative study is made for response versus time for different spring and damper types at three important frequency ratios: one at r = 1, one at r > 1 and one at r <1.
Keywords: shock absorber; untuned vibration damper; frequency ratios; non-linear springs; non-linear dampers; stability; boundary value problem; multisegment method of integration